Kriminalisasi Ekspresi dan Politik Teror: Kritik terhadap Praktik Pembatasan Kebebasan Berpendapat dalam Sistem Ketatanegaraan Indonesia - Aini Shalihah; Yenny Ermita; Novi Enjelina Putri; Annisa Firdhausy; Wahyu Fahmi Rizaldy (Journal of Law and Administrative Science, 2026)
Freedom of expression is a constitutional right of citizens guaranteed within Indonesia’s constitutional system as part of the principles of the rule of law and democracy. However, in practice, this freedom often faces various forms of restrictions that tend to be repressive, including through the criminalization of expression and the practice of political terror. This article aims to critically examine how political terror is used as an instrument of power that results in restrictions on freedom of expression, as well as to assess its compatibility with the principles of constitutional law. This study employs a normative legal methodology using legislative, conceptual, and case-based approaches. The findings of the study indicate that the criminalization of expression whether through regulations open to multiple interpretations or the actions of law enforcement officials has the potential to create a chilling effect that hinders public participation in the democratic sphere. In this context, the politics of terror manifests not only in the form of overt repressive actions but also through legal constructs selectively employed to silence criticism of those in power. This situation highlights a tension between constitutional guarantees and prevailing state practices. Therefore, efforts are needed to reconstruct legal policies that ensure more substantial protection of freedom of expression, as well as to strengthen oversight mechanisms regarding the exercise of state authority so that they align with the principles of constitutional democracy and respect for human rights.